Manifesto for Living in the Anthropocene - Fincher, Ruth; Rose, Deborah Bird, 1946-; Gibson, Katherine (Book collections on Project MUSE., 2020)
The recent 10,000 year history of climatic stability on Earth that enabled the rise of agriculture and domestication, the growth of cities, numerous technological revolutions, and the emergence of modernity is now over. We accept that in the latest phase of this era, modernity is unmaking the stability that enabled its emergence. But we are deeply worried that current responses to this challeng are focused on market-driven solutions and thus have the potential to further endanger our collective commons. Today public debate is polarized. On one hand we are confronted with the immobilizing effects of knowing "the facts" about climate change. On the other we see a powerful will to ignorance and the effects of a pernicious collaboration between climate change skeptics and industry stakeholders. Clearly, to us, the current crisis calls for new ways of thinking and producing knowledge. Our collective inclination has been to go on in an experimental and exploratory mode, in which we refuse to foreclose on options or jump too quickly to "solutions." In this spirit we feel the need to acknowledge the tragedy of anthropogenic climate change. It is important to tap into the emotional richness of grief about extinction and loss without getting stuck on the "blame game." Our research must allow for the expression of grief and mourning for what has been and is daily being lost. But it is important to adopt a reparative rather than a purely critical stance toward knowing. Might it be possible to welcome the pain of "knowing" if it led to different ways of working with non-human others, recognizing a confluence of desire across the human/non-human divide and the vital rhythms that animate the world? We think that we can work against singular and global representations of "the problem" in the face of which any small, multiple, place-based action is rendered hopeless. We can choose to read for difference rather than dominance; think connectivity rather than hyper-separation; look for multiplicity -- multiple climate changes, multiple ways of living with earth others. We can find ways forward in what is already being done in the here and now; attend to the performative effects of any analysis; tell stories in a hopeful and open way -- allowing for the possibility that life is dormant rather than dead. We can use our critical capacities to recover our rich traditions of counter-culture and theorize them outside the mainstream/alternative binary. All these ways of thinking and researching give rise to new strategies for going forward.